2017
DOI: 10.4081/cp.2017.982
|View full text |Cite
|
Sign up to set email alerts
|

Paraneoplastic Edematous Dermatomyositis: A Rare Syndrome Observed in a Case of Small Cell Lung Cancer

Abstract: Dermatomyositis with subcutaneous edema is a rare process with few reported cases. We report a 63-year-old with lung cancer who presented with an erythematous skin rash and was found to have biopsyproven dermatomyositis. Her course was complicated by generalized edema, myalgias, muscle weakness, dysphagia, and laryngeal edema. The edema was severe and caused respiratory distress requiring intubation. The patient underwent therapy with high-dose glucocorticoids and intravenous immunoglobulin but failed treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 12 publications
(12 reference statements)
1
8
0
3
Order By: Relevance
“…Erythema is classic, appearing on outset or during the evolution of atrophy beaches. Zarrabi et al reported a rare case of edematous paraneoplastic DM with florid subcutaneous edema [12]. In prolonged cases, poïkilo-DM can appear.…”
Section: Discussionmentioning
confidence: 99%
“…Erythema is classic, appearing on outset or during the evolution of atrophy beaches. Zarrabi et al reported a rare case of edematous paraneoplastic DM with florid subcutaneous edema [12]. In prolonged cases, poïkilo-DM can appear.…”
Section: Discussionmentioning
confidence: 99%
“…While periorbital and focal/localized subcutaneous edema especially in poikilodermatous sites is a common feature of DM, more widespread edema, sometimes to the point of anasarca, is considerably rare (24)(25)(26)(27)(28)(29). To date, only 20 or so cases involving juvenile and adult patients with DM presenting with diffuse limb, trunk, and/or generalized subcutaneous edema have been reported in the literature since it was first described by Nitsche in 1988 (24,(30)(31)(32)(33)(34)(35)(36)(37)(38). Most cases are idiopathic but an associated malignancy has been reported in a few (28,32,36,38).…”
Section: Diffuse Subcutaneous Edemamentioning
confidence: 99%
“…Wir stellten in Zusammenschau von Klinik, Histologie und der auffälligen CK-Erhöhung die Diagnose einer bullösen Dermatomyositis (DM). am höchsten und bleibt bis zu fünf Jahre lang erhöht [3,4]. Zu den häufigsten Tumoren bei einer paraneoplastischen DM gehören die soliden Tumoren der Lunge, des Ovars, des Magen-Darm-Trakts, des Pankreas sowie Non-Hodgkin-Lymphome [1,4].…”
Section: Labordiagnostikunclassified
“…Die beschriebenen Hautveränderungen zeigen zum einen charakteristische Zeichen einer DM wie Erytheme im Nacken (shawl sign), im Dekolleté (V-sign), an den Hüften (holster sign), scheckige Hyperpigmentierung (Poikilodermie) und ein zentrofaziales Erythem, während andere typische Hauterscheinungen wie der weinerliche Gesichtsausdruck durch ein charakteristisches fliederfarbenes, periorbitales Ödem (heliotropes Erythem) und erythematöse, lichenoide, konfluierende Papeln über den Metacarpophalangeal-und Interphalangealgelenken (Gottron-Papeln) fehlen [2,5]. Zudem weist der Patient ungewöhnlich seltene Hauterscheinungen einer vesikulobullösen oder erythroödematösen DM auf, die 1951 von Findlay das erste Mal beschrieben wurde und gegenwärtig zunehmend als paraneoplastisches Phänomen diskutiert wird [3,6]. Diese vesikulobullöse Form kann auftreten in Form von kleineren Vesikeln und Erosionen, aber auch in Form von großen Bullae und findet sich oftmals am Stamm, den Extremitäten und im Gesicht [7][8][9], ähnlich wie bei unserem Patienten.…”
Section: Aufgrund Derunclassified